El género Eleocharis R. Brown en Cuba - Zavaro Pérez, Carlos Alberto (1997)
A taxonomic treatment for the Cuban species of the genus Eleocharis R. Brown is presented with dichotomic keys, descriptions of the sections and species, and schemes and distribution maps.